THE FLOUTING OF CONVERSATIONAL MAXIMS IN DEDDY CORBUZIER PODCAST ON YOUTUBE - Sonia Putri Indah; Amrin . Saragih; Isli Iriani Indiah Br. Pane (Universitas Negeri Medan, 2023)
This study was discussed about to investigate the flouting in conversational maxim used by host and guests in Deddy Corbuzier podcast used theory of cooperative principle by Grice. This article was aimed to found how to realization of the flouting maxims in Deddy Corbuzier podcast. This article used Cutting theory to found that strategies to flouting maxims in Deddy Corbuzier podcast. This article applied a qualitative research design method. The data of this research were taken from utterances of the host and guests who flouting maxims. Data was collected using a checklist of three video podcasts by Deddy Corbuzier on the topic of drugs and then analyzed based on the flouting of each maxim.The results have revealed that there are strategies of flouting maxim were realized when speaker using strategies giving too much information, giving too little information, methapor, hyperbole, banter, irony, being obscure, and rhetorical question. And from all of the strategies, the most dominant strategies was namely giving too little information by guest and giving too much information by host.